Приобретение права собственности на плоды, продукцию и доходы по российскому гражданскому праву - Klimowcz, Aleksander (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the acquisition of right in rem in the Russian Federation. The author focus on the selected rights in rem acquisition forms in the Russian civil code in order to present the general principles the lawmaker get.